Analisis kejenuhan peserta didik dalam pembelajaran matematika pada materi perpangkatan (bilangan berpangkat, perkalian dan pembagian pada perpangkatan) secara daring - Putri Nabila Oktarina; Nurkeke Fitriani Kudadiri; Asril Ramadhan (Educenter : Jurnal Ilmiah Pendidikan, 2022)
In the interaction of learning in the school environment, students are inseparable from the problems that exist in the school climate and are regularly able to be owned by students, one of which is fatigue in learning. This study aims to understand the level of saturation of students in learning mathematics on the material of online multiplication, compared to direct learning. The research used quantitative methods with data collection techniques through interviews and tests, using Pre test and Post test instruments. The results of the research at SMPN 04 Medan showed that the learning saturation of ninth grade students was in the moderate category, with a percentage of 45%. This finding indicates the need for more attention to the level of learning saturation to improve learning effectiveness. Furthermore, there is a significant relationship between learning saturation and mathematics learning outcomes of grade IX students, with a moderate correlation and negative relationship. This indicates that the higher the level of learning saturation, the lower the mathematics learning outcomes.